Glenn Gould, Conductor: Critical Reception, Chronicle, and Commentary - Maloney, Timothy (Intersections, 2011)
In 1982, about two months before he died, Glenn Gould conducted a Toronto chamber orchestra to record Richard Wagner’s Siegfried Idyll. Reactions to the recording, eventually released in 1990, varied dramatically: while the Pulitzer Prize–winning critic and Gould scholar Tim Page considered it “a reading of melting and surpassing tenderness,” the composer-conductor Gunther Schuller, also a Pulitzer Prize winner, declared it “the most inept, amateurish, wrong-headed rendition of a major classic ever put to vinyl.” In light of that extreme divergence of opinion, this article examines the recording, Gould’s conducting, and the critical reception to both.